Exploring game grammars: a sociosemiotic account of young people’s game-making practices - Paula, Bruno de (Visual Communication, 2021)
This article investigates the relationship between young people’s game-making practices and meaning-making in videogames. By exploring two different games produced in a game-making club in London through a multimodal sociosemiotic approach, the author discusses how semiotic resources and modes were recruited by participants to realize different discourses. By employing concepts such as modality truth claims and grammar, he examines how these games help us reflect on the links between intertextuality, hegemonic gaming forms and sign-making through digital games. He also outlines how a broader approach to what has been recently defined as the ‘procedural’ mode by Hawreliak in Multimodal Semiotics and Rhetoric in Videogames (2018) can be relevant for promoting different and more democratic forms of meaning-making through videogames.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Decolonizing Game Literacy - Robinson, Petra A.; Williams, Kamala V.; Stojanović, Maja; Paula, Bruno de (Global Citizenship for Adult Education: Advancing Critical Literacies for Equity and Social Justice, 2022)
In the last decades, digital games have moved from niche to mainstream. As more people play, talk about, and engage with these artifacts, they have become an important part of contemporary cultures, giving rise to game literacy—the set of skills needed to meaningfully engage with video games. While the potentials of game literacy have, to some extent, been already discussed in the literature, we have not adequately discussed the need for a game literacy that problematizes the sociocultural dimensions of gaming, including the hegemonic, exclusionary rationales implicitly disseminated through mainstream gaming. In this chapter, I outline a decolonial model for game literacy, remarking how the reflection about the gaming circuits of production and dissemination should be part of any initiative that aims at dealing with critical and creative competences towards gaming, and how these are crucial for any citizen in contemporary societies.
OCLC: 1288078892
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The International Encyclopedia of Media Studies: Media History and the Foundations of Media Studies - Valdivia, Angharad N.; Nerone, John C.; Mayer, Vicki; Mazzarella, Sharon R.; Parameswaran, Radhika E.; Scharrer, Erica; Darling-Wolf, Fabienne; Gates, Kelly (Wiley-Blackwell, 2013)
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Gender, Race, and Class in Media a Critical Reader - Dines, Gail.; Humez, Jean M. (SAGE Publications, 2015)
Incisive analyses of mass media - including such forms as talk shows, MTV, the Internet, soap operas, television sitcoms, dramatic series, pornography, and advertising-enable this provocative third edition of Gender, Race and Class in Media to engage students in critical mass media scholarship. Issues of power related to gender, race, and class are integrated into a wide range of articles examining the economic and cultural implications of mass media as institutions, including the political economy of media production, textual analysis, and media consumption. Throughout, Gender, Race and Class in Media examines the mass media as economic and cultural institutions that shape our social identities, especially in regard to gender, race, and class.
Section: 1 vol. (XIV-761 p.) : ill. ; 26 cm
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Feminism in Play - Gray, Kishonna L.; Voorhees, Gerald; Vossen, Emma (Palgrave Macmillan, 2018)
Feminism in Play focuses on women as they are depicted in video games, as participants in games culture, and as contributors to the games industry. This volume showcases women's resistance to the norms of games culture, as well as women's play and creative practices both in and around the games industry. Contributors analyze the interconnections between games and the broader societal and structural issues impeding the successful inclusion of women in games and games culture. In offering this framework, this volume provides a platform to the silenced and marginalized, offering counter-narratives to the post-racial and post-gendered fantasies that so often obscure the violent context of production and consumption of games culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

First-Person Encounters #3: Prof. Xenia Zeiler - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we interview Xenia Zeiler, an associate professor of South Asian studies at the University of Helsinki, Finland. Her research is situated at the intersection of digital media, religion, and culture, with a focus on India and the worldwide Indian community.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

War Games: Memory, Militarism and the Subject of Play - Hammond, Philip; Pötzsch, Holger (Bloomsbury Publishing USA, 2019)
Many of today's most commercially successful videogames, from Call of Duty to Company of Heroes, are war-themed titles that play out in what are framed as authentic real-world settings inspired by recent news headlines or drawn from history. While such games are marketed as authentic representations of war, they often provide a selective form of realism that eschews problematic, yet salient aspects of war. In addition, changes in the way Western states wage and frame actual wars makes contemporary conflicts increasingly resemble videogames when perceived from the vantage point of Western audiences.This interdisciplinary volume brings together scholars from games studies, media and cultural studies, politics and international relations, and related fields to examine the complex relationships between military-themed videogames and real-world conflict, and to consider how videogames might deal with history, memory, and conflict in alternative ways. It asks: What is the role of videogames in the formation and negotiation of cultural memory of past wars? How do game narratives and designs position the gaming subject in relation to history, war and militarism? And how far do critical, anti-war/peace games offer an alternative or challenge to mainstream commercial titles?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
OCLC: 1104212185
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."–Provided by publisher.
OCLC: 1057550232
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Hybridity, Reflexivity and Mapping: A Collaborative Ethnography of Postcolonial Gameplay - Lammes, Sybille; Smale, Stephanie de (Open Library of Humanities, 2018)
To date, game studies has largely undertheorized the co-production of postcolonial stories, exploration, and mapping in games. Furthermore, as has been noted before (Carr, 2006), the work that has been done on postcolonialism and play so far often leaves the player out of the equation, even sometimes as a theoretical construct. Yet player experience is crucial to understanding such games, as narratives are not only built on the ‘master’ level of game mechanics, but also through the personal stories players processually (Ash, 2009; Thrift, 2008) develop through their journey of touring and mapping, thereby developing spatial stories (De Certeau, 1984; Jenkins, 2004; Lammes, 2009) that may present us with conflicting spatio-temporal accounts. Through a comparative and collaborative auto-ethnographic analysis of Civilization VI (Sid Meier, 2016) – a turn-based strategy game – we want to push this discussion further and improve our theoretical understanding and analytical purchase of the triad relation between narrative and postcolonialism in games, thereby contributing to the field of postcolonial theory and game studies. Drawing on postcolonial geography, science and technology studies (STS), non-representational theory and game studies, we argue that games, through their playful, explorative and emergent qualities, are a powerful means of rethinking and reimagining colonial (hi)stories in this postcolonial era (Lammes, 2009, 2010) including issues of spatio-temporality, cartography and the hybrid relation between women and machines.
Number: 1
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Playing with Being in Digital Asia: Gamic Orientalism and the Virtual Dōjō - Goto-Jones, Chris (Asiascape: Digital Asia, 2015)
Seeking to address the general question, ‘Where is Digital Asia?’, this paper explores the various ways in which the digital and virtual realm interacts with the problematic and contested category of Asia. Beginning with a discussion of the relationship between Asia and Digital Asia, as both cartographic and ideological sites, it moves on to connect Digital Asia with the discourse of techno-Orientalism. Using the example of the videogame as an instance of a digital location that can be visited and explored, this article suggests that the gamic quality of interactivity adds a new, experiential dimension to the ideological structure of (techno-)Orientalism, hence positing the utility of a new form of ‘Gamic Orientalism’. Focussing on the ‘digital dōjō’ as the site of Gamic Orientalism and Digital Asia par excellence, this paper concludes with a discussion of the ways in which gamers represent their engagement with this site in a manner that echoes the way martial artists talk about the significance of their art as self-cultivation. Illustrated with texts from the bushidō canon and interviews with gamers, this playful and experimental piece posits the possibility of ‘virtual bushidō’ as the ultimate expression of Gamic Orientalism, suggesting that Digital Asia is finally located in an ideologically conditioned mode of engagement with the digital medium rather than in any cartographically defined space.
Section: Asiascape: Digital Asia
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 4-Europe (lieu de production du savoir); _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé